Efektivitas Konseling dengan Pendekatan Cognitive-Behavior Therapy untuk Meningkatkan Self-Esteem - Rezki Suci Qamaria (Universitas Islam Tribakti Lirboyo Kediri, 2019)
Self-esteem is one of the essential components that make up an individual's personality. The level of self-esteem possessed by an individual influences the development of self-concept, self-confidence, self-motivation, and personal resilience. Self-esteem develops since the individual realizes its function in the social environment. The case study in this study discusses the condition of one of the students currently studying at the Faculty of Medical of University X of Yogyakarta. The initial assessments used are the intelligence test, personality test, and self-esteem scale. It is concluded that the subject experienced low self-esteem which had an impact on self-confidence, motivation, and resilience ability in attending lectures. This condition also affects the academic achievement of the subject, which is unsatisfactory. This study purpose is to determine the effectiveness of counseling with cognitive-behavioral therapy approach on subjects who have low self-esteem. The techniques used in cognitive-behavioral counseling therapy are ABCDE techniques, Socratic questions, vertical arrows, and relaxation techniques. This study uses a single-case experimental design method. The result is that the subject found some negative beliefs that made him helpless with the situation, especially in academic activities. Then the subject was able to find another positive alternative belief so that the subject had a positive judgment on him. After the counselling process in several sessions, the subject has high self-esteem. The subject has a positive assessment of himself and does not see his weaknesses as a scourge that makes him helpless in carrying out daily activities, especially academic activities